11‐3: Invited Paper: Advanced Micro LED Technologies for AR/MR Systems - Lin, Chien-Chung; Chang, Hsueh-Chih; Kuo, Wei-Hung; Wu, Ming-Hsien; Chao, Chia-Hsin; Fang, Yen-Hsiang (SID International Symposium Digest of technical papers, 2024)
A high quality micro LED array is essential for AR/MR systems. Either transparent or non‐transparent full‐color displays that are better than 3000 PPI require unique integration techniques that need to be optimized. The corresponding effects brought by these photonic components to the systems can be discussed in this talk.